P522 Upadacitinib Promotes Histologic and Endoscopic Mucosal Healing: Results from the Upadacitinib Ulcerative Colitis Phase 3 Program. (21st January 2022) - Peyrin-Biroulet, L; Siegel, C; Tanida, S; Bossuyt, P; Torres, E; Dubinsky, M; Baert, F; Zhou, W; Klaff, J; Berg, S; Laroux, F S; Sanchez Gonzalez, Y; et al.
Abstract: Background: Upadacitinib (UPA), an oral selective and reversible JAK inhibitor, demonstrated significantly greater efficacy compared to placebo (PBO) as treatment for moderate to severe ulcerative colitis (UC), in phase 3 induction (U-ACHIEVE and U-ACCOMPLISH) and maintenance (U-ACHIEVE Maintenance) studies. We evaluated UPA efficacy on histologic outcomes with or without endoscopy in this phase 3 program. The STRIDE II initiative identified histological healing as a treatment target signaling the importance of histologic endpoint inclusion in clinical trials and practice. Methods: The UC phase 3 program were multicenter, double-blind PBO-controlled trials. Induction studies enrolled adult patients with moderate to severe active UC (defined as Adapted Mayo Score of 5–9 points and a centrally reviewed endoscopy subscore of 2–3), with randomization 2:1, UPA 45mg (UPA45) once daily (QD) or PBO. Patients eligible for U-ACHIEVE Maintenance primary analysis (N=451) were clinical responders (per Adapted Mayo score) to 8-weeks (wks) of induction treatment with UPA45. U-ACHIEVE Maintenance patients were randomized 1:1:1 UPA 15mg QD (UPA15): UPA 30mg QD (UPA30): PBO for 52 wks. Endpoints were assessed at wk 8 and/or 52: histological improvement, histologic remission, histologic endoscopic mucosal improvement (HEMI), and mucosal healing (a more stringent endpoint defined as endoscopic score=0 and Geboes score<2.0). For endpoint definitions, see Tables 1 and 2 . Results: Baseline characteristics were similar at wk 0 of induction or maintenance studies. In U-ACHIEVE Induction, patients treated with UPA45 demonstrated a significant increase in histologic improvement (55.0% vs 22.5%), HEMI (30.0% vs 6.6%), and mucosal healing (10.7% vs 1.3%); compared to PBO-treated patients (p< 0.001 for all endpoints, Table1). In U-ACCOMPLISH, patients treated with UPA45 experienced superior efficacy in histologic improvement (62.2% vs 24.5%), HEMI (36.7% vs 5.8%), and mucosal healing (13.5% vs 1.7%) compared to PBO-treated patients (p<0.001 for all endpoints). Significantly higher percentages of patients that received UPA15 and UPA30 (42.8% and 56.9%) at wk 52 demonstrated increased histological improvement compared to PBO-treated patients (20.6%; p<0.001). In addition, patients treated with UPA15 and UPA30 demonstrated superior HEMI (UPA15 34.8%; UPA30 49.3%; PBO 11.8%, p<0.001) and mucosal healing rates (UPA15 17.6%; UPA30 19.0%; PBO 4.7%; p<0.001 for both endpoints). Conclusion: UPA induction and maintenance treatment achieved superior efficacy compared to PBO for all histologic and endoscopic assessments including mucosal healing. [Clinicaltrials.gov, U-ACHIEVE Induction and Maintenance (NCT02819635) and U-ACCOMPLISH (NCT03653026)]